Hampered PdO Redox Dynamics by Water Suppresses Lean Methane Oxidation over Realistic Palladium Catalysts. Issue 17 (26th July 2021) - Velin, Peter; Hemmingsson, Felix; Schaefer, Andreas; Skoglundh, Magnus; Lomachenko, Kirill A.; Raj, Agnes; Thompsett, David; Smedler, Gudmund; Carlsson, Per‐Anders
Abstract: By use of operando spectroscopies under cycling reaction conditions, water is shown to hamper the redox dynamics of realistic palladium oxide nanoparticles dispersed onto alumina and hydrophobic zeolite supports thereby lowering the activity for total oxidation of methane. Water adsorption forms hydroxyl ad‐species that block the methane and oxygen dissociation and seem to prevent lattice oxygen to take part in the methane oxidation. The main catalytic action is thus proposed to shift from the Mars‐van Krevelen mechanism in dry conditions to a slower route that relies on Langmuir‐Hinshelwood type of steps in wet conditions. This key finding has clear implications on catalyst design for low‐temperature gas combustion emission control. Abstract : Realistic Pd Catalyst : Suppressed methane turn‐over frequency caused by hydroxylation of active sites at the rim and on the supported PdO particles. The hydroxylation prevents lattice oxygen to take part in the reaction through inhibition and hampered PdO particle redox dynamics.